Impact of Stigma in Covid-19 Patient: A Litteratur Review - Arif Nurma Etika; Endang Mei Yunalia; Erik Irham Lutfi; Wiwin Sulistyawati (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2020)
Background: Covid - 19 is a disease that has a high virulence so it is easily transmitted, even now it has become a pandemic. Because the impact is mainly for people who have comorbid and also the mortality rate in patients and misleading media, so many people who give stigma to patients and their families. The stigma given to patients suffering from Covid-19 is thought to have a significant impact on the patient. Purpose: Aim of this study to analyze the impact of stigma on patients with Covid-19 Methods: the method used in writing this article is literature review. By using the google scholar search engine, Pubmed, DOAJ, Science Dirrect, Research Gate, with the keywords Covid, impact and Stigma, in 2020, the articles that meet the criteria are 6 articles. Results: Based on the existing analysis, it was found that stigma, both internal stigma and external stigma can affect the mental health of patients with co-19, in addition to other impacts also caused among them are socioeconomic problems Conclusion: It is recommended for health workers to provide mental health support for patients with Covid-19, in addition it is also necessary to have a policy that minimizes the negative impact caused